Peritonsillar abscess: Incidence and current management - García, José Manuel Meléndez (2011)
Introduction: Peritonsillar abscesses are the commonest deep neck infections and are associated with significant morbidity despite the current use o antibiotics.Material and methods: Retrospective study of 198 patients with peritonsillar abscesses diagnosed between 2004 and 2010.Results: The incidence varied between 21 and 37 cases per year with a majority of 106 males, in the total. Ages ranged from 11 to 76 years-old patients and 51,5% of cases had positive history of alcohol consumption or tobacco smoking. Bacteriology showed a predominance of Group A beta-haemolytic Streptococcus and Stahphylococcus aureus.Conclusions: From this study it is recommended that a management protocol, coverage to both aerobic and anaerobic agents should be implemented, as well as it seems not necessary to routinely harvest pus for microbiological tests.